. Peran Putra Putri (PaPi) Farmasi dalam Penyuluhan DAGUSIBU di Desa Danguran: The Role of PaPi Pharmacy in DAGUSIBU Counseling in Danguran Village - Pratama, Muhammad Rizky; Salsabilla, Tegar Vania; Kusuma, Rifa Jivi; Ramadhani, Azzikra Fizaluria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
As an educational institution located in Danguran village, the Surakarta Ministry of Health Poltekkes, Pharmacy Study Program has several programs to increase public knowledge regarding the field of pharmacy and medicine. As part of implementing research into community service activities, requires active involvement of students, not only lecturers, in mentoring activities. One of the newly selected 2024 Boys and Girls of Pharmacy (PaPi) has a program to support campus activities. One of these programs is routine outreach to the community. This counseling has the theme DAGUSIBU, namely GET, USE, SAVE, DISCARD. The target community that will be given counseling is around 40 women from farmer groups. Next is the implementation of DAGUSIBU extension activities which will be held on Thursday, 17 October 2024 using lecture, demonstration, discussion, and question-and-answer methods. Based on the survey results, all description items asked by the public were 100% answered yes. Only in the agreement section that drugs are easily obtained through pharmacies were some respondents who answered no, the percentage figure was 90% answered YES and 10% answered NO. After deepening this through interviews, it was discovered that they preferred to buy medicine at the nearest shop. PaPi's next role is expected to carry out similar activities in other villages in South Klaten District as an implementation of the Tri Dharma of Higher Education through community service activities.